Various Models Of Islamic Economic Fatwa: Critical Analysis Of The Islamic Economic Facing Statement Model In Indonesia, Malaysia, Middle East - Abd. Hadi (Universitas Muhammadiyah Sidoarjo, 2020)
Until now there are many fatwas circulating among Islamic scholars of diverse Islamic law and seem to contradict, especially when comparing between Indonesia, Malaysia and the Middle East. The methodology used in this research is phenomenology that is used to explain the phenomenon that occurs related to the difference of Islamic economic law determination. Then using content analysis to parse and synthesize as well as provide criticism over the various phenomena of various models of determining the fatwa of Islamic economic law. The results of this study, in the context of Islamic economic development, until now there are at least three models of fatwa determination of sharia economic law that has been developed by Islamic economists: (1) Ushl Fiqh Approach (Ushul al-Fiqh as the Basic Determination of Sharia Economic Law) ) Pluralism (Acceptance of the Truth of the West and Islam as the Basis for the Establishment of Sharia Economic Law), (3) Islamization of Conventional Economies (Reducing Non-Syar'i Factors of Conventional Economy as the Basis for the Establishment of Sharia Economic Law). This research will enrich the treasury of Islamic Economics knowledge that is particularly useful for the study of Islamic economic law.